Ideas and perspectives: Can we use the soil carbon saturation deficit to quantitatively assess the soil carbon storage potential, or should we explore other strategies? - Barré, Pierre; Denis, Angers; Basile-Doelsch, Isabelle; Bispo, Antonio; Lauric, Cecillon; Chenu, Claire; Tiphaine, Chevallier; Derrien, Delphine; Thomas, Eglin; Sylvain, Pellerin (Biogeosciences discussions, 2017)
An increase in soil organic carbon stock can contribute to mitigate climate change. International negotiation mechanisms and initiatives call for countries to consider land use change and soil management to achieve atmospheric CO2 removal through storage in terrestrial systems (4p1000.org/). As a result, policy makers raised a specific operational question to the soil science community: how much and at which annual rate additional carbon can be stored in soils in different locations? It has been suggested that the ability of a soil to store additional organic carbon can be estimated from its carbon saturation deficit (Csat-def), which is defined as the difference between the maximum amount of carbon that can be associated to its fine (sat-def is not appropriate, at least in its present form, for assessing quantitatively the whole-soil (total) organic carbon storage potential for operational purposes. We then propose alternative approaches based on new opportunities offered by the development of national and international soil monitoring programs (possibly coupled with modelling) that can provide quantitatively relevant estimates of soil total carbon storage potential. This pragmatic approach will require a sustained effort to maintain and develop soil monitoring programs worldwide and research allowing proper use of such a large amount of data.